Semantics, Social Perception, and Usage of the Ethnonyms "Roma" and "Tsyhany" in Present-Day Ukraine - Панченко, Януш; Кючук, Хусейн; Гоманюк, Микола (Київський національний університет імені Тараса Шевченка, 2025)
The article examines the semantics and practices of using the ethnonyms Roma (Romas) and Tsyhany (Gypsies) in Ukraine. It also presents data on how these terms are perceived both among the residents of Ukraine and within the Roma community itself. The main part of the article is devoted to interpreting the results of a sociological study that included in-depth interviews and a survey based on a nationwide online panel. The survey results indicate that both ethnonyms are well known in Ukraine. It was found that the active introduction of the neologism Romas instead of the habitual Tsyhany did not lead to a significant improvement in the image of the Roma ethnic group, which continues to be associated primarily with negative stereotypes and connotations among Ukrainian residents. At the same time, the attempt to replace the ethnonym Tsyhany with Romas nonetheless influenced the perception of the ethnic group, though in an unexpected way. The Roma national minority, previously perceived as a single group, became divided for part of the respondents into two separate groups: Romas and Tsyhany. The referential groups associated with the ethnonyms Romas and Tsyhany, although overlapping in the minds of most respondents, are distinguished by a significant share of Ukraine’s population. The term Romas is perceived as a self-designation of an ethnic group, while Tsyhany is viewed as the name of a social group associated with an asocial lifestyle. Accordingly, the word Tsyhany is linked to a relatively larger number of negative associations than Romas, although the overall balance of positive and negative associations related to both Roma and Tsyhany is strongly tilted toward the negative. It was also found that the full-scale Russian invasion of Ukraine increased the number of positive associations regarding Ukrainian Roma/Tsyhany, adding perceptions of Roma/Tsyhany as people who, within their means, contribute to the defense of Ukraine.

У статті досліджено семантику та практики використання етнонімів роми і цигани в Україні. Також узагальнено дані щодо сприйняття цих назв як серед мешканців України, так і всередині ромської спільноти. Основну частину статті присвячено інтерпретації результатів соціологічного дослідження, яке охоплювало низку глибинних інтерв’ю та масове опитування на основі загальнонаціональної онлайнової панелі. За результатами опитування можна констатувати, що обидва етноніми відомі жителям України. З’ясовано, що активне впровадження неологізма роми замість усталеної назви цигани, не призвело до істотного покращення іміджу ромської етногрупи, яка серед мешканців України продовжує пов’язуватися переважно з негативними стереотипами та асоціаціями. Водночас спроба замінити етнонім цигани на роми все ж таки вплинула на сприйняття етногрупи, але в неочікуваний спосіб. Ромська національна меншина, яку раніше сприймали як єдину групу, для частини населення розділилася на дві окремі групи – на ромів і на циган. Референтні групи етнонімів роми і цигани, хоча і перетинаються у свідомості більшості опитаних, для частини населення України розрізняються. До того ж слово роми сприймають як самоназву етнічної групи, а цигани — як назву соціальної групи, пов’язаної з асоціальним способом життя. Відповідно, щодо слова цигани фіксуємо більшу кількість негативних асоціацій, ніж щодо роми, хоча баланс суми позитивних і негативних асоціацій, пов’язаних як зі словом роми, так і з назвою цигани, істотно зміщений у бік негативних. Також з’ясовано, що повномасштабне вторгнення Росії в Україну збільшило кількість позитивних асоціацій щодо українських ромів/циган, до яких додалися уявлення про ромів/циган як людей, які в міру можливостей допомагають захищати Україну.
Семантика, соціальне сприйняття та використання етнонімів "роми" і "цигани" у сучасній Україні
Keywords: ethnonym; Roma (Romas); Tsyhany (Gypsies); Ukraine; stereotypes; етнонім; рома (роми); цигани; Україна; стереотипи